Anti-inflammatory effect and mechanism of action of ellagic acid-3, 3′, 4-trimethoxy-4′-O-α-L-rhamnopyranoside isolated from Hopea parviflora in lipopolysaccharide-stimulated RAW 264.7 macrophages. Issue 18 (17th September 2021) - Prabha, B.; Sini, S.; Priyadarshini, T. S.; Sasikumar, P.; Gopalan, Greeshma; Joseph, Jayesh P.; Jithin, M. M.; Sivan, V. V.; Jayamurthy, P.; Radhakrishnan, K. V.
Abstract: Phytochemical investigation of the stem bark of Hopea parviflora resulted in the isolation of 9 compounds; which includes friedelin (1 ), friedelin-3 β -ol (2 ), (-)-ampelopsin A (3 ), (-)- ɛ -viniferin (4 ), (-)-hopeaphenol (5 ), vaticaphenol A (6 ), 2, 4, 8-trihydroxyphenanthrene-2- O -glucoside (7 ), ellagic acid-3, 3', 4-trimethoxy-4'- O -α-L-rhamnopyranoside (8 ) and β -sitosterol- β -D-glucoside (9 ). Among them, compounds 1, 2, 6, 7, 8 and 9 are isolated for the first time from this species. Further, we evaluated the anti-inflammatory activity of compounds 4, 5, 6, 7 and 8 . In this study, compound 8 inhibited the activity of proinflammatory mediators like NO, TNF- α, IL-6, 5-LOX and COX-2, also promoted the action of anti-inflammatory mediator like IL-10 via inhibition of the NF-κB pathway in LPS-stimulated RAW 264.7 macrophages. Graphical Abstract: